The social of representations parents on male teaching in a kindergarten in Tabasco, México - Peña Bermúdez , Nilda Elena de la (2022)
Social representations allow people to perceive the world around them, relate to others and communicate with each other This article is based on qualitative research on the social representations of parents of a Kindergarten, where a series of prejudices faced by male teachers when performing their duties at this school level. Among the findings of this investigation are that: parents are not trusting the work of the male teacher, because they fear that he may harm their children or that he may not be able to perform his function effectively, as he would a female teacher. On the other hand, educational authorities are doing very little about it. These social representations could be given as a result of the experiences, customs and traditions that have been transmitted from generation to generation, which require special attention so as not to affect the work of male teachers at the Preschool level.